Effects of magnesium-modified biochar on soil organic carbon mineralization in citrus orchard - Hu, Lening; Huang, Rui; Zhou, Liming; Qin, Rui; He, Xunyang; Deng, Hua; Li, Ke (Frontiers in Microbiology, 2023)
In order to investigate the carbon sequestration potential of biochar on soil, citrus orchard soils with a forest age of 5 years was taken as the research object, citrus peel biochar (OBC) and magnesium-modified citrus peel biochar (OBC-mg) were selected as additive materials, and organic carbon mineralization experiments were carried out in citrus orchard soil. OBC and OBC-Mg were applied to citrus orchard soils at four application rates (0%, 1%, 2%, and 4%), and incubated at a constant temperature for 100 days. Compared with CK, the cumulative mineralization of soil organic carbon decreased by 5.11% with 1% OBC and 2.14% with 1% OBC-Mg. The application of OBC and OBC-Mg significantly increased the content of soil organic carbon fraction, while the content of soil organic carbon fraction was higher in OBC-Mg treated soil than in OBC treated soil. Meanwhile, the cumulative mineralization of soil organic carbon was significantly and positively correlated with the activities of soil catalase, urease and sucrase. The enzyme activities increased with the cumulative mineralization of organic carbon, and the enzyme activities of the OBC-Mg treated soil were significantly higher than those of the OBC treated soil. The results indicated that the OBC-Mg treatment inhibited the organic carbon mineralization in citrus orchard soils and was more favorable to the increase of soil organic carbon fraction. The Mg-modified approach improved the carbon sequestration potential of biochar for citrus orchard soils and provided favorable support for the theory of soil carbon sink in orchards.